PENGARUH PEMBERIAN ENDORPHIN MASSAGE TERHADAP SKALA NYERI IBU BERSALIN DI BPM LU’LUATUL MUBRIKOH, S.ST BANGKALAN - Nailufar Firdaus (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2018)
Labor is identical to the pain that will be experienced. Physiologically, pain occurs when the muscles of the uterus contract as an effort to open the cervix and push the baby's head towards the pelvis. Based on preliminary studies conducted at the BPM Lu’luatul Mubrikoh, Bangkalan S.ST was obtained from 20 womengiving birth, 4 (20%) of the mothers giving birth experienced severe labor pain. The purpose of this study was to analyze the effect of giving endorphin massage on the scale of maternal pain. The design used in this study was to use a pre-experimental design with the One group pretest post test variable is endorphin massage while the dependent variable is labor pain. The study population was all 16 maternity mothers with a sample of 15 respondents using non-probability sampling and purposive sampling. Data analysis using univariate analysis normality test and bivariate analysis. The research measuring instrument is the observation sheet analyzedwith statistical tests paired t-test or Wilcoxon Signed Rank Test. The results showed that of the 15 respondents given endorphin massage therapy, before being given therapy on average the respondents experienced labor pain with a scale of 6. Whereas after being given endorphin massage therapy the average maternity experience the intensity of labor pain on a painscale 5. There were 4 people significant reduction in pain, not significant 8, and 3 people with constant pain intensity. The results of the Wicoxon Signed Rank Test statistical test showed ρ value 0.005 which means that α <0.05 Ho was rejected Ha accepted, which means that there are differences in the scale of pain before and after giving endorphin massage to the mother. Health workers should provide the best service to maternity mothers, including one of them trying to overcome or reduce labor pain by various methods